Service and Product Quality as Drivers Costumer Satisfaction at Haus Drink in Bekasi - Aflah Harits adzaldi; Muhammad Izzudin Zaki; Fatik Rahayu (Sekolah Tinggi Ilmu Ekonomi Y.A.I - Jakarta - Indonesia, 2025)
This research aims to test whether there is an influence of service quality and product quality on consumer satisfaction at Haus Drink in Bekasi. Based on expectancy disconfirmation theory (EDT). Theory is used to understand how satisfaction and dissatisfaction are derived. This research uses primary data and samples through the non-probability sampling method using the slovin formula, data was obtained for 7 days through google form to Haus consumers in Bekasi from a total of 100 respondents. The analysis uses an outer model, an inner model, and a hypothesis test. Novelty in the researcher used the smart-PLS 3.2.9 application, then the previous research used the SPSS application. The results of the hypothesis test show that consumer satisfaction is positively influenced by the service quality of Haus products and the quality of products has a positive effect on consumer satisfaction of Haus products. The implications of the research for stores to be able to offer loyalty programs, the use of print media such as brochures, posters, pamphlets, banners, and with a storytelling approach to build emotional appeal. After improving these aspects, it is hoped that stores can increase consumer loyalty and satisfaction. produk terhadap kepuasan konsumen pada minuman Haus di Bekasi. Berlandaskan teori yang mendukung tentang kualitas pelayanan dan kualitas produk, dan kepuasan konsumen. Riset ini memakai data primer dan sampel melalui metode non-probability sampling dengan menggunakan rumus slovin, data didapatkan selama 7 hari melalui google form kepada konsumen Haus di Bekasi dari jumlah responden sebanyak 100. Analisis menggunakan outer model, inner model, dan uji hipotesis. Novelty pada peneliti menggunakan aplikasi smart-PLS 3.2.9, kemudian riset terdahulu menggunakan aplikasi SPSS. Hasil uji hipotesis menunjukkan bahwa kepuasan kosumen dipengaruhi secara positif terhadap kualitas pelayanan produk minuman Haus dan kualitas produk berpengaruh positif terhadap kepuasan konsumen produk minuman Haus. Implikasi dari penelitian bagi toko untuk dapat menawarkan program loyalitas, penggunaan media cetak seperti brosur, poster, pamflet, spanduk, dan dengan pendekatan storytelling untuk membangun daya tarik emosional. Setelah memperbaiki aspek-aspek ini, diharapkan toko dapat menaikan loyalitas dan kepuasan konsumen.